Method for improving performance of perovskite solar cell by using fluoroaniline / difluoroaniline molecules and application thereof
By adding fluorine aniline/diofluoride molecules to perovskite solar cells, its amino and fluoropic characteristics are used to solve the problem of insufficient water resistance of perovskite solar cells, and performance improvement and stability are enhanced.
Patent Information
- Application Number
- CN202411469396.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The prior art is difficult to effectively improve the moisture resistance of perovskite solar cells, affecting their performance and stability.
By adding fluorine aniline/diofluorine aniline molecules to the anteromosis of the perovskite solar cell solar cell, the combination of amino group and unpacking PB2+, the hydrophobic and hydrogen bonds of fluorinels, reduce defect density, inhibit halogen ion migration migration And improving the dampness resistance of perovskite.
Effectively improve the moisture resistance of perovskite solar cells, improve its photoelectricity and stability, and enhance the overall performance of the device.
Smart Images

Figure CN119384196A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of perovskite solar cells, and in particular to a method for improving the performance of perovskite solar cells by utilizing fluoroaniline / difluoroaniline molecules. Background Art
[0002] Organic molecules containing amino, carbonyl, cyano, sulfur, and fluorine atoms can passivate defects and improve the optoelectronic properties and stability of perovskite films. However, most organic molecules are electrically insulating or do not match the energy levels of perovskites or transport layers, which affects the effective extraction and transfer of charges within the device. Studies have shown that conjugated molecules can passivate defects and adjust energy levels to promote carrier transfer in devices, and stabilize perovskite interfaces and lattices by inhibiting ion migration.
[0003] At present, conjugated molecules often contain only one or a single passivation site, and the types of such passivation groups are mainly concentrated in amino or carbonyl groups. At present, conjugated molecules often contain only one or a single passivation site, and the types of such passivation groups are mainly concentrated in amino or carbonyl groups. Therefore, such molecules can only passivate a single type of defect and have fewer passivation sites; and such molecules have weak hydrophobic properties and cannot effectively improve the moisture resistance of perovskites. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the existing method for improving the performance of perovskite solar cells cannot effectively improve the moisture resistance of perovskite. The present invention provides a method that can effectively improve the moisture resistance of perovskite.
[0005] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions:
[0006] A method for improving the performance of perovskite solar cells by using fluoroaniline / difluoroaniline molecules, comprising the following steps: S1, providing a substrate and pre-treating it to obtain a pre-treated substrate; S2, spin-coating a SnO2 nanocrystal solution on the pre-treated substrate to obtain an electron transport layer; S3, spin-coating a modified PbI2 solution on the upper part of the electron transport layer and annealing at a preset temperature for a certain time to obtain a first treated part; S4, spin-coating an organic salt solution on the surface of the first treated part, and then spin-coating a Spiro-MeOTAD solution as a hole transport layer; S5, evaporating an electrode on the surface of the hole transport layer.
[0007] Furthermore, in S1, the substrate is a transparent conductive substrate that can withstand high temperatures above 150°C.
[0008] Furthermore, in S1, the pretreatment is to clean the substrate with UV light and ozone for 10 to 18 minutes.
[0009] Furthermore, in S3, the modified PbI2 solution is a PbI2 solution to which fluoroaniline or difluoroaniline is added.
[0010] Furthermore, the concentration of PbI2 in the PbI2 solution is 1-1.5 mol / ml, the added concentration of fluoroaniline is: 0.025-0.15 mol of fluoroaniline per 1 mol of PbI2, and the added concentration of difluoroaniline is: 0.01-0.03 mol of difluoroaniline per 1 mol of PbI2.
[0011] Furthermore, in S3, the preset temperature is 65-75°C, and the annealing time is 1-1.5 minutes. The annealing time is preferably
[0012] Furthermore, in S4, the organic salt solution contains 70-110 mg FAI and 5-15 mg MACl per ml of solution.
[0013] Furthermore, in S4, the preparation method of the Spiro-MeOTAD solution is to add 80-130 mg of Spiro-MeOTAD, 30-60 ul of TBP, and 20-40 ul of LiTFSI solution to every 1 ml of chlorobenzene.
[0014] Furthermore, in S4, the electrode is an Ag electrode with a thickness of 80 to 120 nm.
[0015] The present invention also provides an application of a method for improving the performance of a perovskite solar cell by utilizing fluoroaniline / difluoroaniline molecules, wherein the method is used for preparing a perovskite solar cell.
[0016] Compared with the prior art, the advantages of the present invention are:
[0017] 1. The present invention relates to a method for improving the performance of perovskite solar cells by using fluoroaniline / difluoroaniline molecules. Fluoroaniline / difluoroaniline molecules are added to the perovskite precursor of the perovskite solar cell. First, the defect density can be effectively reduced by combining with the uncoordinated Pb2+ through the amino group; in addition, the amino group can form hydrogen bonds with the halides in the perovskite, especially the uncoordinated I- ions, to inhibit the migration of halogen ions; in addition, the hydrophobicity of the fluorine group can effectively improve the moisture resistance of the perovskite; on the other hand, the fluorine group can form hydrogen bonds with the organic cations of the perovskite to stabilize the lattice structure. The method of the present invention can effectively improve the moisture resistance of the perovskite and has advantages.
[0018] 2. The present invention relates to an application of a method for improving the performance of perovskite solar cells using fluoroaniline / difluoroaniline molecules. The method is simple, widely applicable, and has a large application space. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The scanning electron microscope image of the device 1-3 prepared in the embodiment of the present invention is shown in FIG. Figure 1 (a) is a comparative example of a perovskite film without added molecules, Figure 1 (b) is the perovskite film after adding 2FA in Example 1,
[0020] Figure 1 (c) is the perovskite film after adding 26FA in Example 2.
[0021] Figure 2 This is a diagram of device efficiency corresponding to different fluoroaniline addition concentrations in Experimental Example 2 of the present invention.
[0022] Figure 3 This is a diagram of device efficiency corresponding to different difluoroaniline addition concentrations in Experimental Example 2 of the present invention.
[0023] Figure 4 This is an X-ray diffraction diagram of the perovskite crystal structure at different fluoroaniline addition concentrations in Experimental Example 3 of the present invention.
[0024] Figure 5 This is an X-ray diffraction diagram of the perovskite crystal structure at different difluoroaniline addition concentrations in Experimental Example 3 of the present invention.
[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0026] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. DETAILED DESCRIPTION
[0027] The present invention provides a method for improving the performance of perovskite solar cells by utilizing fluoroaniline / difluoroaniline molecules, comprising the following steps: S1, providing a substrate and pre-treating the substrate to obtain a pre-treated substrate; S2, spin-coating a SnO2 nanocrystal solution on the pre-treated substrate to obtain an electron transport layer; S3, spin-coating a modified PbI2 solution on the upper part of the electron transport layer and annealing at a preset temperature for a certain time to obtain a first treated part; S4, spin-coating an organic salt solution on the surface of the first treated part, and then spin-coating a Spiro-MeOTAD solution as a hole transport layer; S5, evaporating an electrode on the surface of the hole transport layer.
[0028] It can be understood that the method of improving the performance of perovskite solar cells of the present invention adds fluoroaniline / difluoroaniline molecules to the perovskite precursor of the perovskite solar cell. First, the defect density can be effectively reduced by combining with the uncoordinated Pb2+ through the amino group; in addition, the amino group can form hydrogen bonds with the halides in the perovskite, especially the uncoordinated I- ions, to inhibit the migration of halogen ions; in addition, the hydrophobicity of the fluorine group can effectively improve the moisture resistance of the perovskite; on the other hand, the fluorine group can form hydrogen bonds with the organic cations of the perovskite to stabilize the lattice structure.
[0029] (1) The amino group combines with uncoordinated Pb2+ to reduce the defect density; in addition, the amino group can form hydrogen bonds with the halides in the perovskite, especially the uncoordinated I- ions, to inhibit the migration of halogen ions. (2) The hydrophobicity of the fluorine group can improve the moisture resistance of the perovskite; on the other hand, the fluorine group can form hydrogen bonds with the organic cations of the perovskite to stabilize the lattice structure. (3) Both fluoroaniline and difluoroaniline molecules can react with PbI2 solution to form crystal nuclei to promote the growth of perovskite crystals. (4) Fluoroaniline or difluoroaniline can effectively reduce the excess PbI2 content in the perovskite and improve the stability of the device (lead iodide has poor photostability).
[0030] In some embodiments of the present invention, in S1, the substrate is a transparent conductive substrate that can withstand high temperatures above 150° C. Specifically, in some embodiments, the substrate is preferably an ITO / FTO substrate.
[0031] In certain embodiments of the present invention, in S1, the pretreatment is to clean the substrate with UV light and ozone for 10 to 18 minutes.
[0032] In certain embodiments of the present invention, in S3, the modified PbI2 solution is a PbI2 solution to which fluoroaniline or difluoroaniline is added.
[0033] In certain embodiments of the present invention, the concentration of PbI2 in the PbI2 solution is 1-1.5 mol / ml, the concentration of fluoroaniline added is: 0.025-0.15 mol of fluoroaniline added per 1 mol of PbI2, and the concentration of difluoroaniline added is: 0.01-0.03 mol of difluoroaniline added per 1 mol of PbI2. Specifically, the concentration of PbI2 in the PbI2 solution is 1.5 mol / ml, and the concentration of fluoroaniline is 0.075 mol / ml or 0.015 mol / ml of difluoroaniline.
[0034] In some embodiments of the present invention, in S3, the preset temperature is 65-75° C., and the annealing time is 1-1.5 minutes.
[0035] In certain embodiments of the present invention, in said S4, the organic salt solution contains 70-110 mg FAI and 5-15 mg MACl per ml of solution.
[0036] In certain embodiments of the present invention, in S4, the preparation method of the Spiro-MeOTAD solution is to add 80-130 mg of Spiro-MeOTAD, 30-60 ul of TBP, and 20-40 ul of LiTFSI solution to every 1 ml of chlorobenzene, wherein the LiTFSI solution is 520 mg of LiTFSI dissolved in 1 ml of anhydrous acetonitrile, and the cobalt salt solution is 30-60 ul of cobalt salt (FK209) dissolved in 300 mg of cobalt salt (FK209) in 1 ml of anhydrous acetonitrile.
[0037] In some embodiments of the present invention, in S4, the electrode is an Ag electrode of 80-120 nm. Specifically, the electrode is preferably an Ag electrode of 100 nm.
[0038] The present invention also provides an application of a method for improving the performance of a perovskite solar cell using fluoroaniline / difluoroaniline molecules, wherein the method is used for preparing a perovskite solar cell. The method of the present invention is simple, has wide applicability, and has a large application space.
[0039] Example 1
[0040] 1.1 Device preparation process
[0041] In this embodiment, the specific operations are:
[0042] (1) The ITO / FTO substrate is UV cleaned in a UV light and ozone cleaning machine for 15 minutes to remove impurities on the substrate surface and improve the substrate wettability;
[0043] (2) Spin coating SnO2 nanocrystal solution as electron transport layer;
[0044] (3) Spin coating of a PbI2 solution containing 2FA o-fluoroaniline. The concentration of PbI2 in the PbI2 solution is 1.5 mol / ml, and the concentration of fluoroaniline added is: 0.075 mol of fluoroaniline per 1 mol of PbI2. Annealing is then performed on a hot plate at 70°C for 1 min.
[0045] (4) Spin coating of organic salt solution (each ml of solution contains 90 mg FAI and 10 mg MACl);
[0046] (5) Spin coating of Spiro-MeOTAD solution as a hole transport layer;
[0047] (6) A 100 nm thick Ag electrode was deposited to obtain device 1.
[0048] Example 2
[0049] 2.1 Device preparation process
[0050] The specific operations are:
[0051] (1) The ITO / FTO substrate is UV cleaned in a UV light and ozone cleaning machine for 15 minutes to remove impurities on the substrate surface and improve the substrate wettability;
[0052] (2) Spin coating SnO2 nanocrystal solution as electron transport layer;
[0053] (3) Spin coating of a PbI2 solution containing 26FA2 and 6-difluoroaniline (PbI2 concentration was 1.5 mol / ml and difluoroaniline concentration was 0.015 mol / ml), followed by annealing on a hot plate at 70 °C for 1 min;
[0054] (4) Spin coating of organic salt solution (each ml of solution contains 90 mg FAI and 10 mg MACl);
[0055] (5) Spin coating of Spiro-MeOTAD solution as a hole transport layer;
[0056] (6) A 100 nm thick Ag electrode was deposited to obtain device 2.
[0057] Comparative Example 1
[0058] 3.1 Device preparation process
[0059] The specific operations are:
[0060] (1) The ITO / FTO substrate is UV cleaned in a UV light and ozone cleaning machine for 15 minutes to remove impurities on the substrate surface and improve the substrate wettability;
[0061] (2) Spin coating SnO2 nanocrystal solution as electron transport layer;
[0062] (3) No molecules were added and annealed on a hot plate at 70 °C for 1 min;
[0063] (4) Spin coating of organic salt solution (each ml of solution contains 90 mg of FAI and 10 mg of MACl);
[0064] (5) Spin coating of Spiro-MeOTAD solution as a hole transport layer;
[0065] (6) A 100 nm thick Ag electrode was deposited to obtain device 3.
[0066] Experimental Example 1 Scanning electron microscope characterization of the devices 1, 2 and 3 prepared in Example 1, Example 2 and Comparative Example
[0067] 1.1 Test operation
[0068] The device 1 prepared in Example 1 was characterized by scanning electron microscopy, and the results are shown in Figure 1 (b).
[0069] The device 2 prepared in Example 2 was characterized by scanning electron microscopy, and the results are shown in Figure 1 (c).
[0070] The device 3 prepared in the comparative example was characterized by scanning electron microscopy, and the results are shown in Figure 1 (a).
[0071] 1.2 Results Analysis
[0072] See also Figure 1 (a) Figure 1 (b) Figure 1 (c) It can be seen that, compared with the device 3 prepared in comparative example 1, the perovskite crystal sizes of the devices 1 and 2 prepared in examples 1 and 2 are more uniform, the grains are larger, and the PbI2 content is less.
[0073] This is because PbI2 will decompose under light and destroy the device. It can be seen that after adding fluoroaniline and difluoroaniline molecules, the fluoroaniline and difluoroaniline molecules react with the PbI2 solution, the PbI2 content is reduced, and the stability of the device is improved. In addition, the fluoroaniline and difluoroaniline molecules react with the PbI2 solution to form crystal nuclei that promote the growth of perovskite crystals, so that the resulting perovskite grains are larger, the surface morphology is better, and there are fewer defects.
[0074] Experimental Example 2: Investigating the Effect of Addition Concentration of Fluoroaniline and Difluoroaniline on the Crystal Structure of Perovskite 2.1 Experimental Operation
[0075] The concentrations of fluoroaniline added were adjusted to different values (0%, 6%, 7%, 8%, 9%) to obtain five groups of samples 1 to 5. The concentrations of difluoroaniline added were adjusted to different values (0%, 1%, 2%, 3%, 4%) to obtain five groups of samples 6 to 10.
[0076] 2.2 Results Analysis
[0077] See also Figure 2 and Figure 3 From the device efficiency diagram, it can be seen that the optimal addition concentration of fluoroaniline is 0.075 mol / ml, and the optimal addition concentration of difluoroaniline is 0.015 mol / ml.
[0078] Moreover, for samples 1-10, the overall performance of the devices with the addition of fluoroaniline or difluoroaniline was improved, with the highest functional conversion efficiency reaching 25.02%.
[0079] Experimental Example 3: Investigating the effects of fluoroaniline and difluoroaniline on the crystal structure of perovskite
[0080] 3.1 Test operation
[0081] Adjust different fluoroaniline addition concentrations (concentrations are 0%, 5%, 7%, 10%, 14%) to obtain five groups of samples 1-5, and use XRD X-ray diffraction to analyze the perovskite crystal structure of samples 1-5. The analysis results are shown in Figure 4 .
[0082] Adjusting different difluoroaniline addition concentrations (concentrations are 0%, 1%, 3%, 5%) to obtain four groups of samples 1-4, and using XRD X-ray diffraction to analyze the perovskite crystal structure of samples 1-4, the analysis results are shown in Figure 4 .
[0083] 3.2 Results Analysis
[0084] Figure 4 , Figure 5 They are the XRD spectra of perovskite layer with different concentrations of 2FA and 26FA added.
[0085] Among them, the diffraction peak of PbI2 appears at 12.4°, while the diffraction peaks of 13.7°, 24.0°, and 27.8° correspond to the (001), (111), and (002) crystal planes of the perovskite FAPbI3, respectively.
[0086] We found that as the amount of 2FA and 26FA added increased, the peak intensity of PbI2 decreased; while the diffraction peaks of FAPbI3 (001) and (002) crystal planes increased. This means that adding 2FA and 26FA can indeed promote perovskite crystallization, reduce the PbI2 content, and obtain perovskite films with better photoelectric properties and stability. Therefore, in this case, the performance of perovskite solar cells can be effectively improved by adding fluoroaniline / difluoroaniline molecules.
[0087] In summary, the present invention relates to a method for improving the performance of perovskite solar cells using fluoroaniline / difluoroaniline molecules. The amino group combines with uncoordinated Pb2+ to effectively reduce the defect density; in addition, the amino group can form hydrogen bonds with halides in the perovskite, especially uncoordinated I- ions, to inhibit the migration of halogen ions; in addition, the hydrophobicity of the fluorine group can effectively improve the moisture resistance of the perovskite; on the other hand, the fluorine group can form hydrogen bonds with the organic cations of the perovskite to stabilize the lattice structure. The method of the present invention can effectively improve the moisture resistance of the perovskite and has advantages.
[0088] The above embodiment is only one implementation of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A method for improving the performance of perovskite solar cells using fluoroaniline / difluoroaniline molecules, characterized in that: The following steps are involved: S1, providing a substrate and pre-treating the substrate to obtain a pre-treated substrate; S2. Spin-coating SnO2 nanocrystal solution on the pretreated substrate to obtain an electron transport layer; S3. Spin-coating modified PbI2 solution on the upper part of the electron transport layer and annealing at a preset temperature for a certain period of time to obtain a first treated part; S4. Spin-coating an organic salt solution on the surface of the first treated part, and then spin-coating a Spiro-MeOTAD solution as a hole transport layer; S5. Evaporating an electrode on the surface of the hole transport layer.
2. The method of improving the performance of perovskite solar cells by using fluoroaniline / difluoroaniline molecules according to claim 1, characterized in that: In the above S1, the substrate is a transparent conductive substrate that can withstand high temperatures above 150°C.
3. The method of improving the performance of perovskite solar cells by using fluoroaniline / difluoroaniline molecules according to claim 1, characterized in that: In S1, the pretreatment is to clean the substrate with UV light and ozone for 10 to 18 minutes.
4. The method of improving the performance of perovskite solar cells by using fluoroaniline / difluoroaniline molecules according to claim 1, characterized in that: In S3, the modified PbI2 solution is a PbI2 solution to which fluoroaniline or difluoroaniline is added.
5. The method of improving the performance of perovskite solar cells by using fluoroaniline / difluoroaniline molecules according to claim 4, characterized in that: The concentration of PbI2 in the PbI2 solution is 1-1.5 mol / ml, the added concentration of fluoroaniline is: 0.025-0.15 mol of fluoroaniline per 1 mol of PbI2, and the added concentration of difluoroaniline is: 0.01-0.03 mol of difluoroaniline per 1 mol of PbI2.
6. The method of claim 1 for improving the performance of perovskite solar cells using fluoroaniline / difluoroaniline molecules, characterized in that: In S3, the preset temperature is 65-75° C., and the annealing time is 1-1.5 minutes.
7. The method of claim 1 for improving the performance of perovskite solar cells using fluoroaniline / difluoroaniline molecules, characterized in that: In the S4, the organic salt solution contains 70-110 mg FAI and 5-15 mg MACl per ml of solution.
8. The method of improving the performance of perovskite solar cells by using fluoroaniline / difluoroaniline molecules according to claim 1, characterized in that: In S4, the preparation method of the Spiro-MeOTAD solution is as follows: 80-130 mg of Spiro-MeOTAD, 30-60 ul of TBP, and 20-40 ul of LiTFSI solution are added to every 1 ml of chlorobenzene.
9. The method of improving the performance of perovskite solar cells by using fluoroaniline / difluoroaniline molecules according to claim 1, characterized in that: In the S4, the electrode is an Ag electrode with a thickness of 80 to 120 nm.
10. The use of a method for improving the performance of perovskite solar cells using fluoroaniline / difluoroaniline molecules according to any one of claims 1 to 9, characterized in that: The method is used for preparing perovskite solar cells.
Citation Information
Patent Citations
Method for passivating perovskite thin film layer and perovskite solar cell
CN112467038A
Benzamide bromide modification-based perovskite solar cell and preparation method thereof
CN116234331A
Perovskite layer, solar cell, laminated cell and preparation method and application thereof
CN118042898A
Perovskite solar cell and preparation method therefor and electric device
WO2023123390A1